Fusion of Vesicular Stomatitis Virus with the Cytoplasmic Membrane of L Cells - Heine, Jochen W. (1969)
At an early stage in infection, vesicular stomatitis viruses were attached to the surface of L cells by fusion of the viral and cell membranes.